Association of moral values with vaccine hesitancy. (December 2017) - Amin, Avnika; Bednarczyk, Robert; Ray, Cara; Melchiori, Kala; Graham, Jesse; Huntsinger, Jeffrey; Omer, Saad
Abstract Clusters of unvaccinated children are particularly susceptible to outbreaks of vaccine-preventable disease1, 2 . Existing messaging interventions demonstrate short-term success, but some may backfire and worsen vaccine hesitancy3 . Values-based messages appeal to core morality, which influences the attitudes individuals then have on topics like vaccination4–7 . We must understand how underlying morals, not just attitudes, differ by hesitancy type to develop interventions that work with individual values. Here, we show in two correlational studies that harm and fairness foundations are not significantly associated with vaccine hesitancy, but purity and liberty foundations are. We found that medium-hesitancy parents were twice as likely as low-hesitancy parents to highly emphasize purity (adjusted odds ratio: 2.08; 95% confidence interval: 1.27–3.40). High-hesitancy respondents were twice as likely to strongly emphasize purity (adjusted odds ratio: 2.15; 95% confidence interval: 1.39–3.31) and liberty (adjusted odds ratio: 2.19; 95% confidence interval: 1.50–3.21). Our results demonstrate that endorsement of harm and fairness—ideas often emphasized in traditional vaccine-focused messages—are not predictive of vaccine hesitancy. This, combined with significant associations of purity and liberty with hesitancy, indicates a need for inclusion of broader themes in vaccine discussions. These findings have the potential for application to other health decisions and communications as well. Two surveys of a large cohort of US parents find that concerns about purity and liberty are strongly associated with vaccine hesitancy. This suggests that vaccination campaigns may be more effective by targeting these moral values.